A Different Approach to The Modern Sport Administration: Method of İnnovation. - Atalay, A, Yücel, A. S, Boztepe, E. (My University, 2013)
Today, it is known that sport has made a significant progress associated with its transition into a visual product and increasing needs of the people to keep fit and for healthy life as well as developing information technology and a growing leisure culture. As a social institution, sport’s presence of an ever-growing structure in economic and cultural organizations has necessitated this social phenomenon’s reappraisal when the changing economic and social conditions of the world have been taken into consideration. Thus, sport has its share from the incidents in the process of globalization that has made the conditions for international competition and free market economy, and the world’s transform into a single market dominant. To survive in today's rapidly changing competitive environment, companies should constantly change and renew their products, services and production methods. In this context, a new and age appropriate administrative mentality emerging in recent years has begun to be used. This governance model is innovation. It is defined as the use of new methods in social cultural and administrative environment. Innovation, a persistent administration model means meeting the individual and social needs at a better level. By means of Innovation meaning of the word means renewal, or innovation, companies have been developing administrative strategies for sectoral mobility by following the requirements of the age. However, the point emphasized here the use of innovation as a method converted into economic and social value added not as the new one. With the developing technology, it is ever inevitable to form sport clubs into a structure that is competitive and could produce goods and services, acting fast and flexible, harmonising with changes and transformations within the scope of innovation method of administration. These innovation methods, which could be applied in sport based, not also could enlarge the scope of sport clubs but also constitute a powerful and proactive structure that carry out its assignments and responsibilities. In this direction, ıt is aimed in this study to examine the applicability of the innovation administration model, one of the different administration models which are the necessities of developing economic life at sports clubs. Also, it is tried to mention the effects of innovation administration for the sustainability of competition in the world of sport industry.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Sport; Sport Management; New Approaches in Sport Management; Innovation in Sport